2017
DOI: 10.1111/nmo.13150
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal high fat diet increases inhibition of dorsal motor nucleus of the vagus neurons regulating gastric functions

Abstract: Background: Previous studies suggest an increased inhibition of dorsal motor nucleus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Our previous studies (Bhagat et al, 2015; McMenamin et al, 2017) previous demonstrated alterations in central vagal neurocircuits in response to a PNHFD. In fact, the intrinsic membrane properties of central vagal neurons are dysfunctional following exposure to a PNHFD, even prior to the onset of obesity; dorsal motor nucleus of the vagus (DMV) neurons that innervate the stomach are less excitable, have a lower membrane input resistance, and fire fewer action potentials in response to depolarizing inputs (Bhagat et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our previous studies (Bhagat et al, 2015; McMenamin et al, 2017) previous demonstrated alterations in central vagal neurocircuits in response to a PNHFD. In fact, the intrinsic membrane properties of central vagal neurons are dysfunctional following exposure to a PNHFD, even prior to the onset of obesity; dorsal motor nucleus of the vagus (DMV) neurons that innervate the stomach are less excitable, have a lower membrane input resistance, and fire fewer action potentials in response to depolarizing inputs (Bhagat et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, the intrinsic membrane properties of central vagal neurons are dysfunctional following exposure to a PNHFD, even prior to the onset of obesity; dorsal motor nucleus of the vagus (DMV) neurons that innervate the stomach are less excitable, have a lower membrane input resistance, and fire fewer action potentials in response to depolarizing inputs (Bhagat et al, 2015). Furthermore PNHFD also induces dysregulation of the synaptic inputs these vagal efferent motoneurons receive, including an increased response to the GABA A receptor antagonist, bicuculline, suggesting an increase in tonic GABAergic synaptic input (McMenamin et al, 2017). It should be noted that, while DMV neurons are spontaneously active and display pacemaking properties, firing action potentials at approximately 1 Hz (Travagli & Gillis, 1994), their excitability is sculpted continuously by the variety of synaptic inputs they receive (Travagli et al, 1991; Davis et al, 2004; Babic et al, 2011) most notably from the adjacent nucleus of the tractus solitarius (NTS).…”
Section: Discussionmentioning
confidence: 99%
“…Diet can have profound effects on synaptic strength in many areas of the brainstem, including those in the dorsal vagal complex (DVC), which includes the dorsal motor nucleus of the vagus (DMV), the nucleus tractus solitarius (NTS), and the area postrema (AP) (Bhagat et al 2015;Clyburn et al 2018;Kentish et al 2012Kentish et al , 2016McMenamin et al 2018;Travagli and Anselmi 2016;Troy et al 2016). DVC neurocircuits are responsible for integrating and responding to peripheral sensory information from cardiovascular, respiratory, and gastrointestinal (GI) systems (Lu and Bieger 1998;Travagli and Anselmi 2016).…”
Section: Brainstemmentioning
confidence: 99%
“…Indeed, several studies have suggests that acute neuroinflammation is protective against a wide range of insults, including hemorrhage, whereas chronic neuroinflammation induces significant damage and disruption to neurocircuit function (Astiz et al 2017;Burda and Sofroniew 2014). Chronic HFD exposure and DIO, for example, decrease vagal motoneuron excitability, alter neuronal morphology, and inhibit the CCK-induced modulation of synaptic transmission (Bhagat et al 2015;McMenamin et al 2018).…”
Section: Brainstemmentioning
confidence: 99%
See 1 more Smart Citation